2000
DOI: 10.1097/00126334-200002010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infectious HIV in Circulating Monocytes From Patients on Prolonged Highly Active Antiretroviral Therapy

Abstract: The existence of a reservoir of resting CD4+ T cells harboring latent replication-competent HIV has been demonstrated in patients on prolonged highly active antiretroviral therapy (HAART). Latently infected tissue macrophages may constitute a second HIV reservoir. The pool of these cells may be maintained by incoming infected monocytes from blood and/or by in situ viral replication. In this study, the presence of infectious HIV was investigated in highly purified monocytes from 5 patients receiving HAART with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(62 citation statements)
references
References 19 publications
0
60
0
1
Order By: Relevance
“…In HIV infection, both nonclassical and intermediate monocytes are infected and expanded. Furthermore, HIV-infected monocytes and macrophages can be found in patients with no detectable plasma viral loads (57,58).…”
Section: Cd16mentioning
confidence: 99%
“…In HIV infection, both nonclassical and intermediate monocytes are infected and expanded. Furthermore, HIV-infected monocytes and macrophages can be found in patients with no detectable plasma viral loads (57,58).…”
Section: Cd16mentioning
confidence: 99%
“…Monocytes productively infected with HIV have been found in the peripheral blood and constitute a significant, continually evolving viral reservoir (20)(21)(22)(23)(24). These infected monocytes can further differentiate in the tissues into mature, virus-harboring macrophages that can disseminate HIV to other cell types, including T cells (15,22,25).…”
Section: Cd16mentioning
confidence: 99%
“…Myeloid cell types especially are thought to be a minor latent-HIV-1 reservoir population compared to CD4 T lymphoid cells, which are considered a major population. Although clinical studies have indicated the existence of HIV-1 latency in myeloid cells and ex vivo analysis also indicated the potential of myeloid cells as a latent-HIV-1 reservoir, the establishment of an optimal model of HIV-1 latency reflecting HIV/AIDS patients is required (60)(61)(62). Recently, a latent HIV-1 infection model was established by using isolated CD4 T cells from peripheral blood mononuclear cells (63,64).…”
Section: Discussionmentioning
confidence: 99%